Ambient backscatter communications technology for batteryless IoT - Qin TAO; Caijun ZHONG; Zhaoyang ZHANG (物联网学报)
As one of the core enabling technologies supporting the batteryless Internet of things(IoT),ambient backscattering communication technology has the characteristics of low power consumption and low cost.Firstly,the basic concept of ambient backscattering communication technology and the research status at home and abroad were introduced.Then,based on an in-depth analysis of the differences between ambient backscattering communication technology and RFID technology,the technical difficulties faced by the ambient backscattering communication system were described in detail,including large detection delay,high bit error rate,low transmission rate and short communication distance.In addition,a series of potential solutions to the challenges were proposed.Finally,the future research directions of ambient backscattering communication were prospected.